The Swing Theory of Islam: A Study of Ernest Gellner Epistemology - Supriyanto Supriyanto (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2022)
Theory is the highest form of knowledge. As for the person who succeeds in giving birth to a theory, he can be said to be someone who really deserves ‘appreciation’. Gellner as a sociologist managed to read the social reality of Islam by giving birth to the pendulum swing theory in Islam - A Pendulum Swing Theory of Islam. This article tries to explain Ernest Gellner’s theory. From studies conducted show that: 1) His theory was born from his interest in Islam, for him Islam has a structure and character that is unique compared to religion outside, 2) The ability of Islam to respond to change without losing ‘identity’ makes the social response of Muslims in a level that ‘established.’ This second point, for Gellner, is the key to why Muslims’ social reality movements tend to ‘flux and reflux of religion’ as well as the Pendulum swing.